Effects of U.S. inflation rates on Fruitful Rim beef cow-calf production input costs - Brauman, Callie (Kansas State University, 2024)
The United States relies on the beef industry for both import and export beef; however, the overall U.S. cattle herd size is the lowest it has been since 1954 due to wide variety of factors discussed in this analysis. The United States is one of the top beef exporters in the world, providing beef to many countries. This is also a crucial area of income for the U.S. Due to the increased cost of production and lower profit margins, there have been many herd liquidations across the country, having a negative impact on the national herd size. There are many factors that have affected beef cattle production's overall profitability within the last several years, including but not limited to weather, lack of succession planning, age of cattle producers, global events, and consumer habits. With an increasing inflation rate, many producers are unable to continue beef cattle production due to their inability to financially afford the resources and supplies needed to produce beef cattle, while also providing for their families and covering the increased cost of living. Aside from these things, many cattle producers, as well as other agricultural producers have always been able to rely on lenders to provide capital, allowing them to cover their operating costs until they receive payment for their product. It is the goal of this study to provide insight through analysis determining the effects of United States inflation on cow-calf production input costs within the Fruitful Rim region. This study uses data analysis through both correlation and regression methods. This analysis focuses on data pertaining to cow-calf producers within the Fruitful Rim Region, collected annually by the U.S. Department of Agriculture and the National Agriculture Statistics Services. The data included numerous categories of input costs as well as the Consumer Price Index (CPI) from 1996 to 2022 to analyze the correlation between the input costs and in inflation rates. Through this analysis it was discovered that certain input costs are more affected by changes in inflation than others. For example, there was little to no correlation between the CPI and vet/medicine costs; however, purchased feed cost was directly correlated with the CPI. Purchased feed costs increased $0.55 per head with one unit of increase in the CPI. Cattle for backgrounding were inversely related to the CPI and showed a $0.46 decrease per head of cattle when there was one unit of increase in the CPI. Producers can focus on more affected areas and be less concerned about costs that may not change much. For example, there is no direct correlation between veterinary and medicine costs and the CPI. Therefore, when inflation is increasing this would not be a cost to be as concerned with; however, the results show that purchased feed costs increase with CPI increases. Producers can focus on alternative means of feed, such as grazed feed, to save input costs when inflation is increasing. The information discovered and summarized in this study provides guidance to producers interested in making educated decisions in different economic situations. As the data shows, there are some categories of input costs that are highly affected by changes in inflation; however, there are others that are not affected at all.
Keywords: Inflation; Cattle production; Fruitful Rim; Cow-calf; Agriculture